If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 10z + -14 + -2z + -9z = -5 Reorder the terms: 1 + -14 + 10z + -2z + -9z = -5 Combine like terms: 1 + -14 = -13 -13 + 10z + -2z + -9z = -5 Combine like terms: 10z + -2z = 8z -13 + 8z + -9z = -5 Combine like terms: 8z + -9z = -1z -13 + -1z = -5 Solving -13 + -1z = -5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1z = -5 + 13 Combine like terms: -13 + 13 = 0 0 + -1z = -5 + 13 -1z = -5 + 13 Combine like terms: -5 + 13 = 8 -1z = 8 Divide each side by '-1'. z = -8 Simplifying z = -8
| 0.1(40)+0.7x=0.5(40+x) | | A+3=22-8 | | .30(5x-9)=4 | | A+3=22-4*2 | | 9(2x+5)=0 | | -12-5x+2x^2=0 | | 2h-14=-14 | | 4+5x=2x+3 | | 7k^2+19k-6=0 | | 7x^2+70x-9=0 | | -6+-7x+x^3=0 | | 5.95+.19l=15.83 | | 4(-4t^2+22t+1)=100 | | y=ln(7x^2+3y^2) | | 4y=-5x+28 | | 0.13(5x-9)=4 | | 23-17= | | .13(5x-9)=4 | | 6j+5j/3=5/3 | | 22h+500=1204 | | 4x-7=x-1 | | 6w-1=-19 | | x+3/2-4x+6/5=1/2 | | 10+7c=42 | | 10+7c=32 | | 14+2y/2=y+14/4 | | -8q-11=9 | | -1+3x+7x=-81 | | 12v+9/6+8v+12/9=2/3 | | X+7-2x=12 | | (1+a)= | | 6.99+.55p=11.94 |